2013
DOI: 10.1007/s10815-013-9955-7
|View full text |Cite
|
Sign up to set email alerts
|

Seminal plasma insemination during ovum-pickup—a method to increase pregnancy rate in IVF/ICSI procedure. A pilot randomized trial

Abstract: Purpose In IVF procedures, endometrial function is a limiting factor of the pregnancy rate and the aims of this study is to determine whether seminal plasma insemination at ovum pick-up in IVF has any effect on pregnancy rate. Methods We designed a single center, 2 parallel groups, randomized pilot study. All couples undergoing an IVF procedure in our clinic between January 2010 and December 2011 were considered for enrollment in the study. The patients who met the inclusion criteria were randomized into two g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…The flow of study identification is shown in Figure . Eight RCTs on women undergoing IVF (2128 in total) were identified as relevant and included in the meta‐analysis . No quasi‐randomized trials were identified.…”
Section: Resultsmentioning
confidence: 99%
“…The flow of study identification is shown in Figure . Eight RCTs on women undergoing IVF (2128 in total) were identified as relevant and included in the meta‐analysis . No quasi‐randomized trials were identified.…”
Section: Resultsmentioning
confidence: 99%
“…A possible explanation is that the mode of action of SP has not yet been clarified. As no significant impact on pregnancy rate could be demonstrated, only the potential of improving pregnancy rates has been discussed. In addition, intrauterine instillation of diluted SP at the time of oocyte retrieval failed to show significant impact on pregnancy rate or live‐birth rate per transfer.…”
Section: Discussionmentioning
confidence: 99%
“…SP seems to have the potential to improve pregnancy rates if used intracervically and intravaginally at the time of oocyte collection, although no significant impact has yet been shown. However, Chicea et al found a significantly higher implantation rate when using SP and sexual intercourse; thus, exposure to semen at the embryo peri‐transfer period in an IVF cycle seems to increase the likelihood of successful early embryo implantation and development. Intrauterine instillation of diluted SP at oocyte pick‐up does not increase pregnancy rate or live‐birth rate, most probably owing to the effects of dilution.…”
Section: Introductionmentioning
confidence: 99%
“…The high concentration of proteins involved in fertility present in SP makes them a potential source of male fertility biomarker. In line with the importance of SP in a successful pregnancy, some studies showed that patients who underwent SP intravaginal insemination around the time of ovum pickup or embryo transfer reached higher implantation and clinical pregnancy rates compared to the controls (Chicea, Ispasoiu, & Focsa, ; Crawford, Ray, Gudi, Shah, & Homburg, ; Friedler et al, ).…”
Section: Introductionmentioning
confidence: 89%